Role of a Bacillus subtilis Direct-Fed Microbial on Digesta Viscosity, Bacterial Translocation, and Bone Mineralization in Turkey Poults Fed with a Rye-Based Diet - Latorre, Juan D.; Hernandez-Velasco, Xochitl; Kogut, Michael H.; Vicente, Jose L.; Wolfenden, Ross; Wolfenden, Amanda; Hargis, Billy M.; Kuttappan, Vivek A.; Tellez, Guillermo (Frontiers in Veterinary Science, 2014)
Rye contains high concentrations of non-starch polysaccharides (NSP), leading to reduced digestibility. Since poultry have little or no endogenous enzymes capable of hydrolyzing these NSP, exogenous carbohydrases as feed additives are used in an attempt to reduce the anti-nutritional effects of these polysaccharides. Previously, an in vitro study conducted in our laboratory showed that inclusion of certain Bacillus direct-fed microbial (DFM) candidates that produce exogenous phytase, lipase, protease, cellulase and xylanase in high NSP diets significantly reduced both digesta viscosity and Clostridium perfringens proliferation. In the present study, rye-based turkey starter diets with or without Bacillus-DFM were administered ad libitum to day-of-hatch turkey poults in two independent experiments. In both experiments, day-of-hatch turkey poults were randomly assigned to either a control diet (CON) or a DFM treated diet (n = 25 birds/group). At ten days–of-age, all turkey poults from experiments 1 and 2 were weighted and 12 turkey poults/group were randomly selected and humanely killed. Liver samples were aseptically collected to evaluate bacterial translocation, and intestinal digesta samples were individually collected to evaluate viscosity. Additionally, in experiment 2 both tibias were removed for assessment of bone parameters. In both experiments, the TRT group showed a reduction in the total number of coliforms in the liver as well as a reduced digesta viscosity when compared to the CON group (P<0.05). Turkey poults fed the Bacillus-DFM candidate had increased tibia diameter, breaking strength, ash content, calcium content, and phosphorus content when compared with CON turkey poults. In summary, turkey poults fed with a rye-based diet without DFM showed an increase in bacterial translocation and digesta viscosity, accompanied by a reduction in bone mineralization; however these adverse effects can be prevented by the inclusion of selected a Bacillus-DFM candida